MOLECULAR CHARACTERIZATION OF FRESH WATER ACTINOBACTERIA USING 16S RDNA BASED TECHNIQUE - MADAN MOHAN GUNDA; M.A.SINGARACHRAYA (International Journal of Pharma and Bio Sciences, 2012)
Twenty four isolates of actinomycetes were collected from water and sediment samples of three major fresh water systems of Karimnagar, Andhra Pradesh, India at Lower Manair Dam, Manakondur Pond and Kothapally pond from July 2006 to June 2008. These isolates were screened for their diversity and biological significance. Among them, eight showed good antagonistic activity against ten test bacteria. Two of these eight isolates (LAM1 and LAM2) were found to produce wide spectrum of antibacterial agents. These most potent strains were selected and were subjected to molecular identification. 16S rDNA was successfully amplified from the genome of the selected isolates with 8F and 1492R primers using BDT v3.1 cycle sequencing kit on ABI 3730xl Genetic analyzer. 16S rDNA amplicons of the strains were subjected to automated DNA sequencing. Partial 16S rDNA sequences obtained was compared directly with sequences in the NCBI database using BLAST as well as with the sequences available with Ribosomal Database Project (RDP). The sequence analysis revealed that LAM1 belongs to Streptomyces sp and LAM2 belongs to Micromonospora sp.